SUBLIMINAL MESSAGE OF NAZISM IDEOLOGY IN COMEDY-SATIRE FILM “JOJO RABBIT” - Mappatadang, Andi Siti Nurhaliza; Abdullah, Abdullah; Fitriyani, Fitriyani (State University of Makassar, 2025)
This research is titled “Subliminal Message of Nazism Ideology in Comedy-Satire Film JoJo Rabbit.” Using a qualitative approach and semiotic analysis method, this study reveals how the elements of the film subtly convey Nazism ideology through its narrative, characters, and visual symbols. This research uses a descriptive qualitative method. The data of this study was carried out through direct interviews with viewers who had watched the film